Investigating the performance of nitrogen-doped graphene photoanode in dye-sensitized solar cells - Joseph, E. (American Institute of Physics Inc., 2016)
In this paper, the atmospheric pressure chemical vapor deposition (AP-CVD) is used to synthesize graphene on a copper substrate by utilizing methane as a precursor and N-doped graphene (NDG) in the presence of ammonia. The performance of pure titanium dioxide (TiO2), TiO2/graphene, and TiO2/NDG as photoanodes in dye-sensitized solar cell (DSSC) were compared. Field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) showed flakes of few layers with an interrupted layer in both graphene and NDG. DSSC consist of TiO2/NDG photoanode exhibits a better enhancement due to the high conductivity of donor N in graphene which enhances the electron transportation across nanoporous TiO2. Â© 2016 Author(s).